High-dose proton beam therapy for stage I non-small cell lung cancer: Clinical outcomes and prognostic factors. (March 2015) - Makita, Chiyoko; Nakamura, Tatsuya; Takada, Akinori; Takayama, Kanako; Suzuki, Motohisa; Azami, Yusuke; Kato, Takahiro; Tsukiyama, Iwao; Hareyama, Masato; Kikuchi, Yasuhiro; Daimon, Takashi; Hata, Masaharu; et al.
Abstract Background. Evidence has suggested that radiation therapy with a lower dose per fraction may be a reasonable option for the treatment of centrally located non-small cell lung cancer (NSCLC). The aim of this study was to evaluate the safety and efficacy of two proton beam therapy (PBT) protocols for stage I NSCLC and to determine prognostic factors. Material and methods. This study included patients clinically diagnosed with stage I NSCLC. Based on the location of the tumor, one of the two PBT protocols was administered. Patients with peripherally located tumors were given 66 Gy relative biological dose effectiveness (RBE) over 10 fractions (Protocol A) while patients with centrally located tumors were given 80 Gy (RBE) over 25 fractions (Protocol B). Results. Between January 2009 and May 2012, 56 eligible patients were enrolled (protocol A: 32 patients; protocol B: 24 patients). The three-year overall survival (OS), progression-free survival (PFS), and local control (LC) rates were 81.3% [95% confidence interval (CI) 75.9–86.7%], 73.4% (95% CI 67.2–79.6%), and 96.0% (95% CI 93.2–98.8%), respectively. There were no significant differences in outcomes between the two protocols. Late grade 2 and 3 pulmonary toxicities were observed in nine patients (13.4%) and one patient (1.5%), respectively; no grade 4 or 5 toxicities were observed. Sex, age, performance status, T-stage, operability, and tumor pathology were not associated with OS and PFS. Only maximum standardized uptake value (SUVmax; < 5 vs. ≥ 5) was identified as a significant prognostic factor for OS and PFS. Conclusion. Both high-dose PBT protocols achieved high LC rates with tolerable toxicities in stage I NSCLC patients, and SUVmax was a significant prognostic factor.